LOS CONTEXTOS: INSTITUCIONAL- ORGANIZATIVO Y DIRECTIVO PEDAGOGICOS Y SU INCIDENCIA EN EL RENDIMIENTO ACADEMICO DE LAS ESTUDIANTES DE LA ESCUELA DE BIOQUIMICA Y FARMACIA DE LA ESCUELA SUPERIOR POLITECNICA DE CHIMBORAZO, LINEAMIENTOS DE MEJORAMIENTO. - JAVIER DEFRANC L. (2005)
THE CONTEXTS: INSTITUTIONAL- ORGANIZATIONAL AND PEDAGOGICAL DIRECTIVE AND ITS IMPACT ON THE ACADEMIC PERFORMANCE OF THE STUDENTS OF THE SCHOOL OF BIOCHEMISTRY AND PHARMACY OF THE HIGHER POLYTECHNIC SCHOOL OF CHIMBORAZO, IMPROVEMENT GUIDELINES.